The Perancangan dan Uji Coba Incinerator Sampah Sederhana Sebagai Solusi Pengelolaan Sampah Mandiri di RW 5 Kelurahan Kopo - Hidayat, Rasiman; Safitri, Reni (Jurnal Pengabdian Tri Bhakti, 2025)
This community service program (KKN) was motivated by fundamental issues in RW 5, Kopo village, including an unsustainable waste mangement system, dependence onpaid waste collection services, dan low awareness of waste segregation. The program aimed to iplement an innovative solution in the form of a waste incinerator and conduct supporting activities to empower the community. The methods employed were field observation, and literature study, which were then analyzed using descriptive qualitative analysis. The primary result were the design and testing of a prototype incinerator, powered by used oil, capable of burning 100 kg of waster per hour alongside various educational and social activities. The program,s implications provide an alternative solution for independent waste mangemenet that can reduce the economic burden on resident, increase enviromental awareness, and strengthen collaboration between the university and the community. This initiative is expected to serve as a pilot model for orther regions.